OPTIMIZING THE PERFORMANCE OF CHARGE AIR COOLER (CAC) AS A HEAT TRANSFER MEDIUM TO IMPROVE ENGINE RELIABILITY AT PT PLN NUSANTARA POWER UP ARUN - Abdi, Faisal; Dewi, Ratni; Yunus, Muhammad (Jurnal Sains dan Teknologi Reaksi, 2024)
ABSTRACTEquipment performance is one very important thing to be maintained by a company or related agency in order to keep production or work activities running smoothly. Heat Exchanger is a common equipment that we find in many companies and related agencies. Leakage, corrosiveness is common in a heat exchanger or heat exchanger equipment. PT PLN Nusantara Power has a Charge Air Cooler (HE) as a heat exchanger medium between air for the combustion process and cooling water in each engine to help the electricity production process. For this reason, this analysis aims to see the reliability of engines 1 to 10 seen from the ratio of the effectiveness value of the calculation results to the effectiveness value of the commissioning results and compare the operational parameters in the field with the results of the hysys simulation. From the results of the calculation analysis, the highest effectiveness value on engine 3 was 92.759 % which was influenced by the ratio of the actual heat transfer rate value compared to the maximum heat transfer rate value. This result is of course as expected where the effectiveness value of the air cooler charge must be greater than 90%. Similar to engine 3, the other nine engines also have an effectiveness value of 90%, meaning that in terms of performance the charge air cooler is still able to work optimally. In the input of hysys simulation data, a difference in data between the incoming air temperature data from the data input in hysys and operational data in the field was obtained. This can be caused by the large value of the discharge of the two flows, readings in the field, as well as the need for calibration data in the field for the reading of equipment performance indicators such as flow indications, pressure indicators, temperature indicators, and so onKeywords : Engine, Corrosion, Heat exchanger, effectiveness, hysys